Performance Index Analysis of A 6 DOF Serial And Parallel Mechanism - Yu Qikai; You Youpeng; Han Jiangyi (Jixie chuandong)
The Jacobian matrix of a 6 DOF serial and parallel mechanism is established.At the bottom of mechanism is based on Delta mechanism,the top of mechanism is a spherical 2 DOF five bars and a independent 1 DOF rotating composite mechanism.The three dexterity index is analyzed,and the comprehensive dexterity index is defined.According to the requirements of different application can be different weights in the mechanism of three kinds of dexterity index,and the variation in its working space is analyzed,and it is simulated with MATLAB,the results can be applied to the machine mechanism optimization synthesis and trajectory planning.